Conversation Analysis of Repair and Adjacency Pairs on An Interview with Russian President Vladimir Putin in NBC News America - Kukuh Tri Laksono; Brigitta Septarini Rahmasari; Agita Risma Nurhikmawati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
Conversation is one of the essential parts of communication that needs skills and knowledge between participants. Many errors happen while people are in conversation. The crucial factors are conversation more spontaneously and many aspects influencing communication. Therefore, this study aims to reveal the process of conversation using theories of conversation analysis repair and adjacency pairs by Brian Paltridge (2012) in NBC News Interview with Vladimir Putin. The documentation method is used to collect the data. The data source is collected from an English transcription interview between Keir Simmons and Vladimir Putin accessed on the official website NBC News. Qualitative content analysis is used as a technique for analysing the data. The results of this study show 39 data of repairs, 32 self-initiated self-repair, 2 self-initiated other-repair, and 5 other-initiated self-repairs. As for adjacency pairs, show a total of 52 data, 28 questions-answers, 16 assessment-agreement, 5 request-agreement, 2 blame-denial, 1 offer-acceptance, and 1 closing-leaving. In conclusion, the interview ran well despite using different languages in conversation and limited times. Furthermore, the interviewee's institutional background influenced the process of interview.